Using Residual Blood from the Arterial Blood Gas Test to Perform Therapeutic Drug Monitoring of Vancomycin: An Example of Good Clinical Practice Moving towards a Sustainable Intensive Care Unit. (27th December 2022) - Smeets, T. J. L.; van de Velde, D.; Koch, B. C. P.; Endeman, H.; Hunfeld, N. G. M.
Abstract : Background . Regarding sustainability in the intensive care unit (ICU), there is increasing interest in reducing material waste and avoiding unnecessary procedures. Therapeutic drug monitoring (TDM) of vancomycin, using a dedicated tube, is standard clinical care during treatment with vancomycin. Furthermore, in the ICU, on a daily basis, arterial blood gas (ABG) tests are frequently performed throughout the day. After analysis, a variable volume of blood is discarded. Lithium heparin (LiHep) syringes for ABG tests differ from normally used dipotassium ethylenediaminetetraacetic acid (K2 EDTA) tubes. The primary objective was to compare both containers and validate the use of LiHep syringes. Secondary objectives were to evaluate the potential impact on saving materials, nursing time, and costs when implementing vancomycin TDM via LiHep syringes. Methods . Vancomycin analysis from sampling in lithium heparin (LiHep) syringes for ABG tests was validated and compared with the concentrations from conventional sampling in K2 EDTA tubes. For method comparison, a Bland–Altman plot and Deming regression analysis were performed. The method was validated for inter- and intra-day precision and accuracy. Vancomycin was analyzed by means of the validated method using a particle-enhanced turbidimetric inhibition immunoassay (PETINIA) autoanalyzer. Furthermore, an analysis was conducted to evaluate the potential impact of implementing vancomycin sampling via ABG tests on savings in materials, nursing time, and costs. Results . From 18 patients, 24 plasma samples in both K2 EDTA tubes and LiHep syringes were obtained and compared. The mean relative difference between the two containers was −2.0% (−3.0 to −0.93%). Both the Deming regression analysis and the Bland–Altman plot met the acceptance criteria. Potentially, over 1000 blood draws and accompanying materials and packaging can be saved when vancomycin samples are obtained by means of scavenged LiHep syringes. The vancomycin analysis for LiHep syringes showed a total interday precision of 1.95% and an accuracy of 99.7%. The total intraday precision was 2.22%, and the accuracy was 99.2%. Accuracy and precision values were within the acceptance criteria of recovery 85 to 115% and ≤15%, respectively. Conclusion . No significant differences were found in vancomycin concentration between the two analyses, and the LiHep analysis was validated for further implementation in clinical care. Residual blood from ABG test samples can be used for TDM of vancomycin, resulting in a potential reduction of materials used and the number of blood draws. These results will contribute to a more sustainable TDM process with benefits for the patient.